A Convergent Parallel Study on Knowledge, Perceptions, and Attitudes of Mainstream Workers during COVID-19 - Alshammari, Farhan; Mostoles, Romeo, Jr; Pasay-an, Eddieson; Alshammari, Sultan (UI Scholars Hub, 2021)
Background: This study explores and assesses the knowledge, perceptions, and attitudes of mainstream workers during the COVID-19 pandemic in the Ha’il Region, Kingdom of Saudi Arabia. Methods: Using convergent parallel mixed-methods design, 502 frontline workers were enlisted via snowball and purposive sampling. Descriptive statistics and thematic analysis were used to analyze the quantitative and qualitative data, respectively. Results: There is a well-prepared response to COVID-19, namely, a commendable knowledge, attitude, and practices (KAP) gap documented in reliable information concerning the virus, specifically, awareness that COVID-19 can be a potentially fatal disease (100%); that droplets from infected people (29.8%) can spread the disease; and taking actions to prevent the spread of COVID-19 in the community can save their lives. Four themes and three subthemes yielded: (1) actual, tangible knowledge with subtheme pieces of information; (2) the extent of danger with subtheme uncertainties; (3) precautionary measures; and (4) a yearning to know more, with the subtheme of novel information. Conclusions: Communication among health authorities and at-risk individuals in response to COVID-19 must be facilitated. This is to support those in the healthcare industry in shaping an intervention strategy that emphasizes both preparation and protection.